Legal Implications of Changing Building Use Rights To Ownership Rights - Saputra, I Komang Dedi; Senastri, Ni Made Jaya; Utama, I Wayan Kartika Jaya (Journal of Law, Politic and Humanities, 2026)
The transfer of Building Use Rights to Ownership Rights is an important aspect in the regulation of agrarian law in Indonesia, especially after the issuance of Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration. In this study, the normative legal research method is used. Regulations related to the transfer of Building Use Rights to Ownership Rights are regulated in Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units and Land Registration. Provisions regarding whether or not a Building Use Right can be transferred are stated in Article 45 paragraph (2) of the Article as the basis or basis for someone to change their Rights from Building Use Rights to Ownership Rights. The change of Building Use Rights to Ownership Rights has been clarified in Article 94 of Government Regulation Number 18 of 2021. The form of implementation of Article 48 of Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units and Land Registration and also as an effort to realize the government regulation. Determining priority rights over land in the form of Building Use Rights (HGB) that have expired depends on three factors: the subject of the rights, in terms of who submits the application for the rights, usually the subject of the rights whose name is recorded on the certificate (the former rights holder); the subject of the rights who submits the application must be able to prove that they are truly entitled to the land; and the land use is in accordance with the intent of the granting of the rights in question.